Effect of vegetables and nano-particle hydroxyapatite on the remediation of cadmium and phosphatase activity in rhizosphere soil through immobilization. Issue 6 (12th May 2019) - Zhu, Fang; He, Siying; Shang, Zhifeng
Abstract: Nano-hydroxyapatite (n-HAP) and two types of plants (rape plant and cabbage) were used in this study to investigate their combined remediation effect on the removal of heavy metal contaminated soil. Different n-HAP concentrations (5, 10, 15, 20, and 25 g kg −1 ) with two kinds of plants were used in the experiments and compared with two control groups without adding n-HAP. Compared with the control group, the total Cd concentration increased and the amount of available Cd decreased significantly in soil ( p < 0.05) in text groups. Cd toxicity decreased, and the rape plant and cabbage biomass increased after adding n-HAP. Cd accumulation in rape plant and cabbage decreased when more n-HAP was added; Cd accumulated less in rape plant than in cabbage. The phosphatase activity in soil also increased after adding n-HAP. Results showed that the total Cd concentration was positively correlated with phosphatase activity, the concentration of the available Cd and Cd accumulated in root has a significant effect on phosphatase activity in Cd-contaminated soil ( p < 0.05). Cd-contaminated soil could be remediated effectively with rape plant and n-HAP with a concentration of 15 g kg −1 .